2023
DOI: 10.1073/pnas.2221181120
|View full text |Cite
|
Sign up to set email alerts
|

LEAFY and APETALA1 down-regulate ZINC FINGER PROTEIN 1 and 8 to release their repression on class B and C floral homeotic genes

Abstract: Organ initiation from the shoot apical meristem first gives rise to leaves during vegetative development and then flowers during reproductive development. LEAFY ( LFY ) is activated after floral induction and together with other factors promotes the floral program. LFY functions redundantly with APETALA1 (AP1) to activate the class B genes APETALA3 ( AP3 ) and PISTILLATA ( PI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…ABC genes must also keep quiet during the vegetative phase at the risk of interfering with correct leaf development; this is not simply due to the absence of LFY but also necessitates active silencing of floral homeotic genes ( Goodrich et al 1997 ). Recent studies have started to identify specific factors involved in recruiting polycomb complexes to those loci: for instance, 2 Zinc Fingers were shown to recruit PRC2 to induce heterochromatin formation at APETALA1 , APETALA3 , and AGAMOUS in Arabidopsis ( Hu et al 2023 ). Those factors are repressed by LFY and APETALA1, allowing release of vegetative inhibition once floral induction is set in motion.…”
Section: Swimming Upstreammentioning
confidence: 99%
“…ABC genes must also keep quiet during the vegetative phase at the risk of interfering with correct leaf development; this is not simply due to the absence of LFY but also necessitates active silencing of floral homeotic genes ( Goodrich et al 1997 ). Recent studies have started to identify specific factors involved in recruiting polycomb complexes to those loci: for instance, 2 Zinc Fingers were shown to recruit PRC2 to induce heterochromatin formation at APETALA1 , APETALA3 , and AGAMOUS in Arabidopsis ( Hu et al 2023 ). Those factors are repressed by LFY and APETALA1, allowing release of vegetative inhibition once floral induction is set in motion.…”
Section: Swimming Upstreammentioning
confidence: 99%
“…promoter-reporter fusions with GUS or GFP) are largely identical to each other ( Peiffer et al., 2008 ). Because generating transgenic plants and crossing the transgene into different backgrounds (e.g., mutant backgrounds) is not required, in situ hybridization remains a powerful method for obtaining spatial information about RNA molecules ( Hu et al., 2023 ). A major limitation of in situ hybridization is its low throughput.…”
Section: Floral Meristem Development In 4d: Spatiotemporally Resolved...mentioning
confidence: 99%
“…A recent study reported that LFY and AP1 mediate AP3 , PI , and AG activation by downregulating two zinc finger protein transcription factor genes, Arabidopsis ZINC FINGER PROTEIN1 ( ZP1 ), and ZINC FINGER PROTEIN8 ( ZFP8 ) ( Hu et al., 2023 ). ZP1 has known roles in proper root hair development, while ZP8 is associated with trichome initiation ( Hu et al., 2023 ). Hu and colleagues showed that ZP1 and ZFP8 are transcriptional repressors of AP3 , PI , and AG in leaves during the vegetative stage.…”
Section: Floral Meristem Development In 4d: Spatiotemporally Resolved...mentioning
confidence: 99%
“…Only a very reduced subset of factors and interactions involved in flower development are shown––those most relevant to the work by Hu et al. ( 18 ). Novel interactions are depicted in blue.…”
mentioning
confidence: 98%
“…In PNAS, Hu et al. ( 18 ) report the identification of specific C2H2 zinc finger TFs (ZINC FINGER PROTEIN1, ZP1, and ZINC FINGER PROTEIN 8, ZFP8) that are involved in the repression of AG , AP3, and PI in vegetative tissues and that are themselves down-regulated in developing flowers by LFY and AP1. That is, LFY and AP1, in addition to their role in directly activating in the floral primordia expression of the B and C class organ identity genes, would also up-regulate them indirectly: through the repression of their repressors, ZP1 and ZFP8 .…”
mentioning
confidence: 99%